MEK5, a New Target of the Atypical Protein Kinase C Isoforms in Mitogenic Signaling - Diaz-Meco, María T. (American Society for Microbiology, 2001)
The MEK5–extracellular signal-regulated kinase (ERK5) tandem is a novel mitogen-activated protein kinase cassette critically involved in mitogenic activation by the epidermal growth factor (EGF). The atypical protein kinase C isoforms (aPKCs) have been shown to be required for cell growth and proliferation and have been reported to interact with the adapter protein p62 through a short stretch of acidic amino acids termed the aPKC interaction domain. This region is also present in MEK5, suggesting that it may be an aPKC-binding partner. Here we demonstrate that the aPKCs interact in an EGF-inducible manner with MEK5 and that this interaction is required and sufficient for the activation of MEK5 in response to EGF. Consistent with the role of the aPKCs in the MEK5-ERK5 pathway, we show that ζPKC and λ/ιPKC activate the Jun promoter through the MEF2C element, a well-established target of ERK5. From all these results, we conclude that MEK5 is a critical target of the aPKCs during mitogenic signaling.